MILITARY LEADERSHIP VISION - Gheorghe CALOPĂREANU (Annals: Series on Military Sciences, 2013)
The actual study is aimed at defining the place and the role of the concepts of authority, management and leadership and their connexions within the recognized military strategic systems. In addition to the above mentioned main objective, the following related aims will be achieved in the present work: - to analyze the command, management and leadership nexus; - to make suggestions for configuring an effective professional framework to address the armed forces leadership challenges and the visionary leader concept. Eventually, the present study will emphasize the need for the military leaders to lead not only the members of the organization but the military organizations themselves.